The Devil in the Details: Changes Under Stable Trends of Femicide in Italy During COVID-19 Lockdowns - Cocco, Edoardo (Journal of contemporary criminal justice, 2024)
In recent decades, the issue of violence against women has increasingly drawn the attention of international and national legislators and policymakers. The term “femicide” became widespread in the early 2000s and was incorporated into the criminal codes of several countries. The onset of the COVID-19 pandemic and the subsequent social distancing measures raised significant concerns about their impact on women’s safety. This study examines the effect of COVID-19 confinement measures on femicide trends in Italy, a country which adopted stringent COVID-19 confinement measures and, since 2019, implemented new legislation to counteract violence against women. Using two data sets—one from the Italian Ministry of Interior containing 1,382 cases of female homicides (2013–2022) and another from Italian NGOs detailing 1,253 femicides according to media coverage (2012–2022)—the study employs autoregressive integrated moving average (ARIMA) analysis to assess monthly trends alongside the stringency index for COVID-19 containment efforts. The findings reveal that, although overall femicide rates remained stable during lockdowns, there was a significant shift in victim–perpetrator relationships. Specifically, from March to May 2020, there was a decline in femicides by former partners, offset by an increase in those by cohabiting partners. These results underscore the complexity of femicide and the need for further research on various facets of violence against women. This includes the potential escalation of physical and psychological violence during lockdowns, influenced by forced proximity and substance abuse in domestic environments.